Integration of STEM-Based Learning in Improving Critical Thinking in Mathematics Learning: a Bibliometric Analysis - Mukhammad Rafly Eka Rosyadi; Wildan Fitroni; Muhammad Rizal Rizqullah; Enggar Eko Prasetiyo; Achmad Mujtaba (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze global research trends on the integration of STEM-based learning to improve students’ critical thinking skills in mathematics education during 2021–2025. It seeks to map publication growth, identify dominant keywords, and explore thematic relationships among research topics. Method: A bibliometric analysis was conducted using data from the Scopus database (2021–2025). The study followed five systematic stages: research design, data compilation, analysis, visualization, and interpretation. Keyword mapping was performed using VOSviewer software with terms such as “STEM,” “education,” “critical thinking,” and “mathematics.” Results: A total of 144 relevant articles were identified. The number of publications increased significantly from 2021 to 2025, with “STEM education” emerging as the most dominant keyword. Visualization revealed strong relationships among STEM education, critical thinking, problem solving, and collaborative learning, reflecting a growing global emphasis on developing 21st-century skills through contextual and project-based learning. Novelty: This study presents the first comprehensive bibliometric mapping focused on the intersection between STEM integration and critical thinking in mathematics education. It also highlights emerging research directions integrating digital technology and artificial intelligence (AI) into STEM learning to support innovative, future-oriented educational practices.